Anaerobic curable composition
By using an anaerobic curable composition containing a hydroxy-functionalized mono(meth)acrylate compound and (meth)acrylate functionalized polyurethane resin, the problem of poor effectiveness of traditional compositions when bonding plastics and alloy substrates is solved, and efficient bonding and sealing of different substrates is achieved, especially between metals and plastics.
Patent Information
- Application Number
- CN202510115639.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-11
- Filing Date
- 2020-04-09
- Publication Date
- 2025-04-25
AI Technical Summary
Conventional anaerobic curable compositions are not effective when bonding certain substrates, such as passivation substrates such as plastics and some alloys.
Compositions containing hydroxy-functionalized mono(meth)acrylate compounds, aromatic mono(meth)acrylate compounds, (meth)acrylate functionalized polyurethane resins, and anaerobic cure-induced components are used. The composition provides intermolecular attraction through hydroxy functionalized monomers, promotes long-lasting bonding with metal substrates, and maintains bond flexibility through flexibility of the polyurethane resin.
The composition creates an effective bonding or sealing between different substrates, especially between metals and plastics, significantly improving bond strength and moisture resistance, and is suitable for applications where temperatures are required.
Smart Images

Figure BDA0005257752080000041 
Figure BDA0005257752080000042 
Figure BDA0005257752080000043
Abstract
Description
[0001] This application is a divisional application of the application with application number 202080039991.8 filed on April 9, 2020 and invention name “Anaerobic Curing Composition”. Technical Field
[0002] The present invention relates to an anaerobic curing composition, a method for bonding and / or sealing using the anaerobic curing composition, an assembly bonded or sealed using the anaerobic curing composition, and a cured product of the anaerobic curing composition.
[0003] Brief description of related technology
[0004] Anaerobic curing compositions are generally well known. See, for example, RD Riich, "Anaerobic Adhesives" in Handbook of Adhesive Technology, 29, 467-79, A. Pizzi and K. L. Mittal, eds., Marcel Dekker, Inc., New York (1994), and references cited therein. They are used in a wide variety of applications, and new applications are constantly being developed.
[0005] Anaerobic adhesive systems are those that are stable in the presence of oxygen but polymerize in the absence of oxygen. Polymerization is initiated by the presence of free radicals, usually generated by peroxide compounds. Anaerobic adhesive compositions are well known for their ability to remain in a liquid, unpolymerized state in the presence of oxygen and to cure to a solid state when oxygen is excluded. Due to their ability to cure in an essentially oxygen-free environment, anaerobic curing compositions are widely used as adhesives, sealants, and for bonding materials with closely fitting surfaces.
[0006] Anaerobic adhesive systems often include resin monomers derived according to known polyurethane chemistry, terminated with polymerizable acrylates such as methacrylates, ethacrylates, and chloroacrylates [e.g., polyethylene glycol dimethacrylate and polyurethane-acrylates (e.g., U.S. Pat. No. 3,425,988 (Gorman)]. Other ingredients typically present in anaerobic curable adhesive compositions include initiators (such as organic hydroperoxides, e.g., cumene hydroperoxide, t-butyl hydroperoxide, etc.), accelerators that increase the rate at which the composition cures, and stabilizers such as quinones or hydroquinones, which are included to help prevent premature polymerization of the adhesive due to decomposition of the peroxide compound.
[0007] Desirable cure inducing compositions for inducing and accelerating anaerobic cure may include one or more of saccharin, toluidines (such as N,N-diethyl-p-toluidine ("DE-pT") and N,N-dimethyl-o-toluidine ("DM-oT")), and acetophenylhydrazine ("APH") with maleic acid. See, e.g., U.S. Pat. Nos. 3,218,305 (Krieble), 4,180,640 (Melody), 4,287,330 (Rich), and 4,321,349 (Rich).
[0008] Saccharin and APH are used as standard cure accelerator components in anaerobic adhesive cure systems. In fact, many of the Brand anaerobic adhesive products use either saccharin alone or both saccharin and APH.
[0009] For some applications, it is cumbersome to use anaerobic compositions for bonding. For example, conventional anaerobic curing compositions are ineffective for bonding some substrates, such as passivated substrates such as plastics and some alloys. For such applications, a two-part composition can be formulated. Formulating the composition as a two-part composition allows for greater freedom in selecting components. For example, a curing initiator can be placed in one part of the two-part composition. When the two parts of the composition are put together under suitable anaerobic conditions, the composition cures.
[0010] Activators may also be used for substrates that are difficult to bond using anaerobic curing compositions. Where two substrates are bonded together, the activator may be applied to at least one of the substrates. Thus, for example, where two substrates are bonded together, where at least one of those substrates is a difficult-to-bond substrate, the activator may be applied to either substrate, although it may be desirable to apply it to the difficult-to-bond substrate. Where there is more than one substrate and, for example, where there is more than one difficult-to-bond substrate, it may be desirable to apply the activator to each substrate.
[0011] It would be desirable to provide alternative systems for bonding and methods of bonding using anaerobic curable compositions. Summary of the invention
[0012] In one aspect, the present invention provides an anaerobic curing composition comprising:
[0013] (i) a hydroxy-functional mono(meth)acrylate compound,
[0014] (ii) an aromatic mono(meth)acrylate compound different from the hydroxy-functional mono(meth)acrylate compound,
[0015] (iii) a (meth)acrylate functionalized polyurethane resin, and
[0016] (iv) Anaerobic cure inducing component.
[0017] As used herein, the term "(meth)acrylate" or "(meth)acrylic" refers to acrylate and / or methacrylate species. The term "mono(meth)acrylate" refers to the presence of a single (meth)acrylate group, while the term "multi(meth)acrylate" refers to more than one (meth)acrylate group.
[0018] Multi-(meth)acrylate monomers promote crosslinking in the polymer network and can increase the stiffness of the final cured polymer. This is beneficial in certain applications, especially when performance at elevated temperatures is required. However, in applications involving bonding of dissimilar substrates (e.g. bonding metal to plastic), this increased stiffness has been noted to have a negative impact on performance. Advantageously, the monomers of the present invention are monofunctional in that they contain a mono-(meth)acrylate group, thereby preventing crosslinking and allowing the cured composition to remain flexible and therefore suitable for sealing or bonding applications between dissimilar substrates.
[0019] Advantageously, the composition of the invention is free of methyl methacrylate.
[0020] The hydroxyl-functionalized mono(meth)acrylate compound of the composition of the present invention comprises a mono(meth)acrylate group and a hydroxyl group. Advantageously, the hydroxyl group promotes curing on different active metals by changing the hydrophilicity of the adhesive and improving surface wettability. Metals containing transition metals such as copper and iron promote anaerobic curing. Mild steel has a high level of transition metal iron and cures at a much faster rate than stainless steel (active metal). Brass has a high level of copper, and this also cures at a very fast rate (active metal). On the other hand, stainless steel (inactive metal) has a lower level of iron and a very low level (if any) of copper, and cures much slower than mild steel. Advantageously, the anaerobic curing composition of the present invention provides improved curing properties when cured on an untreated inactive surface, i.e., advantageously, the inactive surface does not need to be treated, such as roughened by chemical or physical wear, or primer is applied to the inactive surface to make it more active.
[0021] Mono(meth)acrylate monomers containing at least one hydroxyl group are used in the present invention to provide intermolecular attraction in the cured polymer and produce a more permanent bond to the metal substrate. Such monomers include hydroxyalkyl(meth)acrylates, ethoxylated and / or propoxylated derivatives thereof, adducts thereof with lactones, polyalkoxy monohydroxy mono(meth)acrylates. Particularly preferred are monomers having C1 to C2 in the alkyl group. 10Hydroxyalkyl (meth)acrylates of carbon atoms, their ethoxylated and / or propoxylated derivatives, their adducts with lactones and their polyalkoxy monohydroxy mono(meth)acrylates.
[0022] Examples of such monomers include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxypentyl (meth)acrylate, hydroxyheptyl (meth)acrylate, hydroxynonyl (meth)acrylate, hydroxydecyl (meth)acrylate, positional isomers thereof, ethoxylated and / or propoxylated derivatives thereof, adducts thereof with lactones, diethylene glycol mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, propylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate.
[0023] The hydroxyl-functionalized mono (meth)acrylate compound of the composition of the present invention comprises one or more suitable (meth)acrylate components which may be selected from those which are (meth)acrylates having the formula:
[0024] H2C=CGCO2R 1 ,
[0025] wherein G may be hydrogen, halogen, or an alkyl group having 1 to about 4 carbon atoms, and R 1 It may be a hydroxyl group having 1 to about 16 carbon atoms.
[0026] The aromatic mono (meth) acrylate compound of the composition of the present invention comprises a mono (meth) acrylate group and an aromatic ring. The aromatic mono (meth) acrylate compound is not a compound identical to a hydroxy-functionalized mono (meth) acrylate compound. Ideally, the aromatic mono (meth) acrylate compound is not hydroxy-functionalized. Beneficially, the monomers selected to have an aromatic ring structure allow the composition to interact with plastic materials that also contain aromatic rings. Such aromatic rings are used as components in a matrix to enhance plastic impregnation. The aromatic ring groups of the monomer allow the composition to interact with, for example, acrylonitrile butadiene styrene, phenolic resins, and polyphenylene sulfide.
[0027] One or more suitable aromatic (meth)acrylate components may be selected from those that are (meth)acrylates having the formula:
[0028] H2C=CGCO2R 1 ,
[0029] wherein G may be hydrogen, halogen, or an alkyl group having 1 to about 4 carbon atoms, and R 1 It may be an aromatic group having 1 to about 14 carbon atoms or a substituted aromatic group having 1 to about 60 carbon atoms.
[0030] The composition of the present invention comprises a (meth)acrylate functionalized polyurethane resin. The (meth)acrylate functionalized polyurethane resin of the composition of the present invention is highly flexible in its cured state. Beneficially, the flexibility of the (meth)acrylate functionalized polyurethane resin provides flexibility to the cured composition and prevents the cured composition from becoming too hard. The composition of the present invention can be used to form a bond or seal between two materials with different coefficients of thermal expansion, such as metal and plastic. When the composition is used to bond or seal two materials with different coefficients of thermal expansion, the (meth)acrylate functionalized polyurethane resin provides the cured composition with flexibility to maintain bonding or sealing. When placed under certain stresses (such as temperature changes), a composition that is too hard may not be able to maintain bonding or sealing.
[0031] The composition of the present invention comprises a curing initiator and an optional curing accelerator. Advantageously, the curing initiator initiates anaerobic curing of the composition. The composition of the present invention may comprise a curing accelerator that accelerates the curing of the composition. When a curing accelerator is present, the composition cures in a shorter amount of time than a composition in which the curing accelerator is not present.
[0032] In the composition of the present invention, the hydroxyl-functionalized mono(meth)acrylate compound comprising a mono(meth)acrylate group and a hydroxyl group may comprise hydroxyethyl(meth)acrylate, for example hydroxyethylmethacrylate:
[0033]
[0034] Advantageously, hydroxyethyl methacrylate contains only one methacrylate, mono(meth)acrylate group. Hydroxyl groups are non-polymerizable in anaerobic environments, so for the purposes of the present invention only the methacrylate group is functional.
[0035] In the composition of the present invention, the hydroxyl-functionalized mono(meth)acrylate compound comprising a mono(meth)acrylate group and a hydroxyl group may be present in an amount of about 5 wt % to about 30 wt % based on the total weight of the composition, for example, the hydroxyl-functionalized mono(meth)acrylate compound may be present in an amount of about 7 wt % to about 15 wt % based on the total weight of the composition.
[0036] In the composition of the present invention, the hydroxyl-functionalized mono(meth)acrylate compound comprising a mono(meth)acrylate group and a hydroxyl group may have a molecular weight of less than about 1000 g / mol, such as less than about 800 g / mol, less than about 600 g / mol, less than about 400 g / mol, or less than about 200 g / mol. Preferably, the hydroxyl-functionalized (meth)acrylate compound may have a molecular weight of about 100 g / mol to about 150 g / mol.
[0037] In the composition of the present invention, the aromatic mono(meth)acrylate compound comprising a mono(meth)acrylate group and an aromatic ring and desirably not hydroxyl functionalized may include benzyl(meth)acrylate, such as benzyl methacrylate:
[0038]
[0039] or furfuryl (meth)acrylates, such as furfuryl methacrylate:
[0040]
[0041] or a combination thereof. Advantageously, benzyl (meth)acrylate or furfuryl (meth)acrylate comprises only one methacrylate, a mono(meth)acrylate group. The aromatic ring structure is non-polymerizable in an anaerobic environment, and therefore for the purposes of the present invention, only the (meth)acrylate group is functional.
[0042] In the composition of the present invention, the aromatic mono(meth)acrylate compound comprising a mono(meth)acrylate group and an aromatic ring may include substituted benzyl(meth)acrylate:
[0043]
[0044] Wherein each R can be independently selected from the following: hydrogen, hydroxyl, alkyl having 1 to about 6 carbon atoms, alkenyl having 1 to about 6 carbon atoms, alkynyl having 1 to about 6 carbon atoms, hydroxyalkyl having 1 to about 6 carbon atoms, hydroxyalkenyl having 1 to about 6 carbon atoms, hydroxyalkynyl having 1 to about 6 carbon atoms, halogen group, amino acid group, carboxyl group or nitro group, or any combination thereof.
[0045] In the composition of the present invention, the aromatic mono(meth)acrylate compound comprising a mono(meth)acrylate group and an aromatic ring may be present in an amount of about 5 wt % to about 60 wt % based on the total weight of the composition, for example, the aromatic mono(meth)acrylate compound may be present in an amount of about 25 wt % to about 40 wt % based on the total weight of the composition.
[0046] In the composition of the present invention, the aromatic mono(meth)acrylate compound comprising a mono(meth)acrylate group and an aromatic ring may have a molecular weight of less than about 1000 g / mol, such as less than about 800 g / mol, less than about 600 g / mol, less than about 400 g / mol, or less than about 200 g / mol. Preferably, the aromatic (meth)acrylate compound may have a molecular weight of about 150 g / mol to about 200 g / mol.
[0047] In the composition of the present invention, the (meth)acrylate functionalized polyurethane resin may be present in an amount of about 20 wt % to about 50 wt % based on the total weight of the composition. Preferably, the (meth)acrylate functionalized polyurethane resin may be present in an amount of about 25 wt % to about 40 wt % based on the total weight of the composition.
[0048] In the composition of the present invention, the (meth)acrylate functionalized polyurethane resin may have a molecular weight of about 5000 to about 7000 g / mol, preferably about 5500 to about 6000 g / mol.
[0049] The anaerobic compositions may also include other conventional components such as free radical initiators, free radical accelerators, free radical generation inhibitors, and metal catalysts such as iron and copper.
[0050] Many well-known free radical polymerization initiators can be added to the compositions of the present invention, including but not limited to hydroperoxides such as CHP, p-menthane hydroperoxide, tert-butyl hydroperoxide ("TBH"), and tert-butyl perbenzoate. Other peroxides include benzoyl peroxide, dibenzoyl peroxide, 1,3-bis(tert-butylperoxyisopropyl)benzene, diacetyl peroxide, 4,4-bis(tert-butylperoxy)butyl valerate, p-chlorobenzoyl peroxide, cumene hydroperoxide, tert-butyl isopropyl peroxide, tert-butyl perbenzoate, di-tert-butyl peroxide, diisopropyl peroxide, 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane, 2,5-dimethyl-2,5-di-tert-butyl-peroxyhexyl-3-yne, 4-methyl-2,2-di-tert-butyl peroxypentane, and combinations thereof.
[0051] Such peroxide compounds are generally useful herein in the range of about 0.1 to about 10 weight percent, based on the total weight of the composition, with about 1 to about 5 weight percent being desirable.
[0052] If desired, the initiator component can be encapsulated. For example, the initiator component can be an encapsulated peroxide, such as encapsulated benzoyl peroxide.
[0053] The composition used in the present invention may further include a thickener and / or a filler. For example, the composition of the present invention may include hydrophobic silica. For example, the composition may further include a polyethylene filler. In the composition of the present invention, a filler (such as a polyethylene filler) may exist in an amount of about 5% by weight to about 15% by weight based on the gross weight of the composition.
[0054] As mentioned above, it should be understood that the compositions used in the present invention may include non-reactive materials, including resins. These components do not participate in the anaerobic curing reaction. They are non-reactive. However, during the curing of other components, these components may become part of the cured product to which they have been added. Examples of such non-reactive materials include: fumed silica, polyethylene, PTFE, mica, polyamide wax, titanium dioxide, barium sulfate.
[0055] The composition of the invention may be thixotropic as measured using a rotational viscometer according to BS EN ISO 3219: 1995. The composition is viscous under static conditions and becomes less viscous when stress is applied, such as when the composition is shaken, agitated, sheared or otherwise stressed.
[0056] The composition of the present invention may have a viscosity of from about 500 mPa·s to about 3000 mPa·s measured at 25°C using BS EN 125092:2001.
[0057] The compositions of the present invention can be used to bond metal to plastic.
[0058] The plastic may optionally be selected from: acrylonitrile butadiene styrene ("ABS"), polycarbonate ("PC"), polycarbonate / acrylonitrile butadiene styrene ("PCABS"), polyaramids, polyamides such as nylon (including nylon 6'6 (("Ny"), (poly[imino(1,6-dioxyhexamethylene)iminohexamethylene])), acrylic plastics, polyvinyl chloride ("PVC") and poly(methyl methacrylate) ("PMMA").
[0059] The metal may optionally be selected from, for example, steel (including mild steel and stainless steel), brass (including watch brass, bronze), or zinc, aluminum, iron, copper, beryllium, cobalt, manganese, nickel, cadmium, gold, silver or alloys thereof. Suitably, the second substrate may be an active substrate containing trace amounts of transition metals.
[0060] The anaerobic curing compositions for use in the present invention may be prepared using conventional methods known to those skilled in the art. For example, the components of the composition may be mixed together in any convenient order consistent with the roles and functions that the components are to perform in the composition. Conventional mixing techniques using known equipment may be applied.
[0061] The present invention also includes cured products formed by anaerobic curing of the compositions of the present invention.
[0062] The method of sealing a joint between a male mating component and a female mating component may be performed by forming a seal for the joint using the cured product of the present invention.
[0063] In one aspect, the present invention provides a method of sealing or bonding a seam between a male mating component and a female mating component, comprising:
[0064] (i) providing a composition according to the present invention;
[0065] (ii) applying the composition to at least one mating component;
[0066] (iii) engaging the mating components to form a seam between the male mating component and the female mating component;
[0067] (iv) and curing the composition such that a joint between the male mating component and the female mating component is sealed by the cured composition.
[0068] The method of the present invention may provide a method of sealing or bonding a joint between a male mating component and a female mating component, wherein one of the male mating component or the female mating component is formed of metal and the other is formed of a plastic material.
[0069] The compositions of the present invention can be used to seal or bond the joint between a male mating component and a female mating component.
[0070] The composition of the present invention can be used to seal or bond a joint between a male mating component and a female mating component, wherein one of the male mating component or the female mating component is formed of metal and the other is formed of a plastic material.
[0071] In one aspect, the present invention provides a sealed or bonded seam assembly comprising male and female mating components that mate together to form a seam and a cured product of a composition of the present invention that forms a seal for the seam. DETAILED DESCRIPTION
[0072] It should be apparent to one of ordinary skill in the art that the embodiments disclosed herein below represent merely illustrative embodiments and that other arrangements and methods capable of reproducing the present invention are possible and included in the present invention.
[0073] experiment
[0074] The components of a representative composition according to the present invention are listed in Table 1:
[0075] Material Weight % (based on the total weight of the composition) Hydroxyethyl Methacrylate 5–30 Benzyl methacrylate 5–40 Methacrylate functionalized polyurethane resin 20–50 PVA beads 0–15 Carboxyethyl acrylate 1–8 Acetylphenylhydrazine 0.1–1 Acidic saccharin 0.1–3 Stabilizer 1 0.01–0.15 Stabilizer 2 0.01–0.25 Polypropylene filler 5–15 Hydrophilic Aerosil 380 1–3 Hydrophobic Aerosil R202 1–2 Aerosil P972 2-4 Tert-Butyl Perbenzoate 0.5–3 Polyethylene glycol monooleate 0–15 Thixatrol ST 0–2 Yellow Dye 0–0.5
[0076] Aerosil: fumed silica available from Evonik Industries;
[0077] Thixatrol ST: A hydroxyl modified aliphatic hydrocarbon available from Elementis Specialities.
[0078] The anaerobic composition was prepared by mixing the materials in Table 1 at room temperature.
[0079] Various compositions within the range listed in Table 1 were used to evaluate the lap shear strength of various substrates.
[0080] Example
[0081] The following compositions were prepared:
[0082]
[0083] Sample compositions according to the invention were tested to determine lap shear strength. The sample compositions were compared to Loctite 577, Loctite 603, Loctite 638, Loctite 648, Loctite 620 and Loctite 6300 from Henkel.
[0084]
[0085] Lap strength test
[0086] The lap strength test was performed according to ASTM D1002-05 (10 / 1 / 2005).
[0087] Breaking torque test
[0088] Breaking torque testing was performed according to ASTM D5649.
[0089] Bonding of metal to PVC
[0090] The bonding of polyvinyl chloride (PVC) to stainless steel was tested for Sample 2. The bonded parts were cured by heat treatment at 80°C for 60 minutes before curing at room temperature for 18 hours. Five independent repetitions (N=5) were performed. Compared to known compositions, the composition of the present invention provides greatly improved bonding of PVC to stainless steel. The results are:
[0091]
[0092] Bonding of metal to nylon
[0093] The bonding of nylon to stainless steel and mild steel was tested for Sample 1. The bonded parts were either cured at room temperature for 24 hours or heat treated at 80°C for 45 minutes before curing at room temperature for 24 hours. The results were:
[0094]
[0095] The bonding of nylon to stainless steel was tested for Sample 2. The bonded parts were cured for 24 hours, or heat treated at 80°C for 45 minutes, followed by curing at room temperature for 18 hours. Five independent replicates (N=5) were performed for each time point. The results were:
[0096]
[0097] After moisture resistance, the bonding of nylon to stainless steel was tested for Sample 2. The bonded parts were cured at 80°C for 45 minutes, then at room temperature for 18 hours, then at 40°C at 98% relative humidity for 72 hours. Five independent replicates (N=5) were performed for each time point. The results are:
[0098]
[0099] The compositions of the present invention provide greatly improved lap shear strength and breaking torque of nylon to stainless steel (non-reactive metal) and mild steel (reactive metal) compared to known compositions. The compositions of the present invention have greatly improved resistance to moisture stress.
[0100] Bonding of metal to polyphenylene sulfide
[0101] The bonding of polyphenylene sulfide to stainless steel and mild steel was tested for Sample 1. The bonded parts were either cured at room temperature for 24 hours or heat treated at 80°C for 45 minutes before curing at room temperature for 24 hours. The composition of the present invention provides greatly improved lap shear strength of polyphenylene sulfide bonded to stainless steel (non-reactive metal) and mild steel (reactive metal) compared to known compositions. The results are:
[0102]
[0103] Bonding of metal to phenolic resin
[0104] The bonding of phenolic resin to stainless steel and mild steel was tested for Sample 1. The bonded parts were either cured at room temperature for 24 hours or heat treated at 80°C for 45 minutes before curing at room temperature for 24 hours. The composition of the present invention provides greatly improved lap shear strength of phenolic resin bonded to stainless steel (non-reactive metal) and mild steel (reactive metal) compared to known compositions. The results are:
[0105]
[0106] Bonding of metal to acrylonitrile butadiene styrene
[0107] Acrylonitrile butadiene styrene was tested for bonding to stainless steel and mild steel for Sample 1. The bonded parts were either cured at room temperature for 24 hours or heat treated at 80°C for 45 minutes before curing at room temperature for 24 hours. The composition of the present invention provides greatly improved lap shear strength of ABS bonded to stainless steel (non-reactive metal) and mild steel (reactive metal) compared to known compositions. The results are:
[0108]
[0109] Metal to Metal Bonding
[0110] Stainless steel to stainless steel bonding was tested for Sample 2. The bonded parts were either cured at room temperature for 24 hours or heat treated at 80°C for 45 minutes before curing at room temperature for 24 hours. The composition of the present invention provides greatly improved breaking torque for stainless steel to stainless steel (non-reactive metal) bonding compared to known compositions. The results are:
[0111]
[0112] When used herein with reference to the present invention, the words "comprises / comprising" and the words "having / including" are used to specify the presence of stated features, integers, steps or components, but do not exclude the presence or addition of one or more other features, integers, steps, components or groups.
[0113] It should be understood that, for clarity, certain features of the present invention described in the context of separate embodiments may also be provided in combination in a single embodiment. On the contrary, for brevity, the various features of the present invention described in the context of a single embodiment may also be provided individually or in any suitable sub-combination.
Claims
1. An anaerobic curing composition comprising: (i) a hydroxy-functional mono(meth)acrylate compound, (ii) an aromatic mono(meth)acrylate compound different from the hydroxy-functional mono(meth)acrylate compound, (iii) a (meth)acrylate functionalized polyurethane resin, and (iv) an anaerobic curing inducing component, The aromatic mono(meth)acrylate compound comprises benzyl methacrylate or furfuryl methacrylate or a combination thereof.
2. The composition of claim 1, wherein the hydroxyl-functionalized mono(meth)acrylate compound comprises hydroxyethyl methacrylate.
3. The composition of any of the preceding claims, wherein the hydroxyl-functional mono (meth)acrylate compound is present in an amount of about 5 wt % to about 30 wt % based on the total weight of the composition.
4. The composition of any of the preceding claims, wherein the hydroxyl-functional mono (meth)acrylate compound is present in an amount of about 7 wt% to about 15 wt% based on the total weight of the composition.
5. The composition of any of the preceding claims, wherein the hydroxyl-functionalized mono (meth)acrylate compound has a molecular weight of less than about 1000 g / mol, such as less than about 800 g / mol, less than about 600 g / mol, less than about 400 g / mol, or less than about 200 g / mol.
6. The composition of any of the preceding claims, wherein the hydroxyl-functional mono (meth)acrylate compound has a molecular weight of about 100 g / mol to about 150 g / mol.
7. The composition of any one of the preceding claims, wherein the aromatic mono (meth)acrylate compound is present in an amount of about 5 wt% to about 60 wt% based on the total weight of the composition.
8. The composition of any one of the preceding claims, wherein the aromatic mono (meth)acrylate compound is present in an amount of about 25 wt% to about 40 wt%, based on the total weight of the composition.
9. The composition of any one of the preceding claims, wherein the aromatic mono(meth)acrylate compound has a molecular weight of less than about 1000 g / mol, such as less than about 800 g / mol, less than about 600 g / mol, less than about 400 g / mol, or less than about 200 g / mol.
10. The composition of any one of the preceding claims, wherein the aromatic mono (meth) acrylate compound has a molecular weight of about 150 g / mol to about 200 g / mol.
11. The composition of any of the preceding claims, wherein the (meth)acrylate functionalized polyurethane resin is present in an amount of about 20 wt% to about 50 wt%, based on the total weight of the composition.
12. The composition of any of the preceding claims, wherein the (meth)acrylate functionalized polyurethane resin is present in an amount of about 25 wt% to about 40 wt%, based on the total weight of the composition.
13. The composition of any of the preceding claims, wherein the (meth)acrylate functionalized polyurethane resin has a molecular weight of about 5000 to about 7000 g / mol, preferably about 5500 to about 6000 g / mol.
14. The composition of any preceding claim, wherein the composition further comprises a polyethylene filler.
15. The composition of claim 14, wherein the polyethylene filler is present in an amount of about 5 wt% to about 15 wt% based on the total weight of the composition.
16. The composition of any one of the preceding claims, wherein the composition further comprises hydrophobic silica.
17. A composition according to any one of the preceding claims, wherein the composition is thixotropic.
18. A composition according to any one of the preceding claims, wherein the composition has a viscosity of from about 500 mPa·s to about 3000 mPa·s measured at 25°C using BS EN 125092:2001.
19. A composition according to any preceding claim for use in bonding metal to plastic.
20. A cured product formed by anaerobic curing of a composition according to any one of the preceding claims.
21. A method of sealing a joint between a male mating component and a female mating component by forming a seal for the joint using the cured product of claim 20.
22. A method of sealing a joint between a male mating component and a female mating component, comprising: (i) providing a composition according to any one of claims 1 to 19; (ii) applying the composition to at least one mating component; (iii) engaging the mating components to form a seam between the male mating component and the female mating component; (iv) and curing the composition such that the joint between the male mating component and the female mating component is sealed by the cured composition; Optionally wherein one of the male or female mating component is formed from metal and the other is formed from a plastics material.
23. Use of a composition according to any one of claims 1 to 18 for sealing a joint between a male mating part and a female mating part; optionally wherein one of the male mating part or the female mating part is formed of metal and the other is formed of a plastic material.
24. A sealed seam assembly comprising male and female mating components that mate together to form a seam, and a cured product of the composition of any one of claims 1 to 19 that forms a seal for the seam.
Citation Information
Patent Citations
Accelerated anaerobic compositions and method of using same
US3218305A
Polyurethane polyacrylate sealant compositions
US3425988A
Accelerator for curable acrylic ester compositions
US4180640A
Accelerator for curable compositions
US4287330A